2015
DOI: 10.17116/oftalma2015131259-63
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor magnetic resonance imaging in the diagnosis of visual pathway neurodegeneration in glaucoma

Abstract: Reduced fractional anisotropy of the lateral geniculate body and optic radiation in patients with glaucoma may be considered an indicator of axonal degeneration at the level of the visual centers. DT-MRI in vivo helps to determine whether or not the neurodegenerative process spreads to the central nervous system as glaucoma progresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
1
Order By: Relevance
“…In addition, reduced FA predicts a smaller lateral geniculate nucleus (LGN) ( 77 ). Some studies also reported reduced FA within the LGN ( 91 ) that correlated to the MDVF ( 78 ). Nevertheless, assessing DTI changes within the LGN, a small subcortical bundle of grey matter, may be less reliable than measuring diffusion changes within white matter.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, reduced FA predicts a smaller lateral geniculate nucleus (LGN) ( 77 ). Some studies also reported reduced FA within the LGN ( 91 ) that correlated to the MDVF ( 78 ). Nevertheless, assessing DTI changes within the LGN, a small subcortical bundle of grey matter, may be less reliable than measuring diffusion changes within white matter.…”
Section: Resultsmentioning
confidence: 98%
“…This possibility is not excluded since the major aqueous humour outflow occurs through the anterior pathways (in particular, through the trabecular (85%) and uveoscleral (5-15%) pathways, and, partially, through the iris) as well as through the posterior pathways (through the vitreous body in the perineural spaces of the optic nerve and perivascular spaces of the retinal vascular system) [23,13]. Since the aqueous humor is produced by the ciliary processes in the posterior chamber and, afterwards, flows to the anterior chamber [3,1], the excess of peroxidation products can get into the aqueous humor from ciliary body, iris, and other tissues due to various pathogenic factors (ocular hypertension, inflammation, etc. ).…”
Section: Resultsmentioning
confidence: 99%
“…Primary open angle glaucoma (POAG) is a polyetiologic disease with a threshold effect and which is associated with many risk factors, including intraocular pressure rates, age, hereditary background, diabetes mellitus, etc.. Primary open angle glaucoma development is caused by metabolic and microstructural changes at the cellular level as a consequence of disorders in involutive and biomechanical processes, insufficient vascular autoregulation and insufficient blood flow, increased nerve cell apoptosis, and decreased natural neuroprotection. The disease is also associated with elastotic characteristics of the sclera, vascular dysregulation, age, changes in immune factors, ethnicity, atherosclerosis, and others [1,2,3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…и соавт. (2015) отметили достоверное снижение значений фракционной анизотропии у 12 пациентов с ПОУГ по сравнению с контрольной группой (медианы 0,74 и 0,77 соответственно, р<0,01) [47].…”
Section: результаты исследований анализирующих структурные изменения ...unclassified